Checking Out Equivalence Within Indonesian – English Bilingual Texts - Bayu Budiharjo (Surakarta English and Literature Journal, 2019)
Establishing equivalence within bilingual texts means saying the same message in different ways. Among numerous theories and views about equivalence is the theory which perceives equivalence as natural or directional. Within the theory, natural equivalence and directional equivalence seem to be quite the opposite but they are in fact interlinked. Bilingual texts composing of Indonesian text and English text are examined to reveal how equivalence, viewed under the framework, works. The examination reveals that the correspondence between constituents of both texts shows the features of: natural equivalence, directional equivalence and non-equivalence. The examination also uncovers the features of both natural equivalence and directional equivalence identified in a single construction. From this study, a brief sketch is obtained that natural equivalence and directional equivalence are not two extremes in the axis of equivalence but both form a tendency in terms of equivalence.